Odpowiedź :
Odpowiedź:
4/ a)2/3 b)-2,1
Szczegółowe wyjaśnienie:
a) 11+3x=13
3x=13-11
3x=2
x=[tex]\frac{2}{3}[/tex] lub (0,6666666666666667)
b) 5x-2,3=-12,8
5x=-12,8+2,3
5x=-10,5
x=-10,5/5
x=-2,1
5/ 6x-x+12=2 prosta postać 5x=-10
5x=2-12 x=-10/5
5x=-10 x=-2
4x-7=23 prosta postać 4x=30
4x=23+7 x=30/4
4x=30 x=7 [tex]\frac{2}{4}[/tex]/2
x=7 1/2
7x-x/3 =8 lub [tex]\frac{7x-x}{3}[/tex]=-8 prosta postać 2x=-8
(6x/3)3=-8 lub [tex]\frac{6x}{3}[/tex]/3=-8 x=-8/2
2x=-8 lub 2x=-8 x=-4
[tex]\frac{1}{3}[/tex]x+3-x=9 prosta postać -[tex]\frac{2}{3}[/tex]x=6
-[tex]\frac{2}{3}[/tex]x+3=9 -[tex]\frac{2}{3}[/tex]x=6 *3
-[tex]\frac{2}{3}[/tex]x=9-3 3*(-[tex]\frac{2}{3}[/tex]x)=18
-[tex]\frac{2}{3}[/tex]x=6 -2x=18/-2
lub -[tex]\frac{2}{3}[/tex]x=[tex]\frac{18}{3}[/tex] x=-9